Synthesis of stationary phases that provide group recognition for polychlorinated biphenyls by porogenic fragment template imprinting - Ndunda, Elizabeth N.; Mizaikoff, Boris (WILEY, 2015)
Molecular recognition based on imprinted polymers results from the polymerization of functional monomers and cross-linkers in the presence of a target analyte (i.e. template), with subsequent removal of the template to create synthetic binding sites. However, complete removal of the template is difficult to achieve, thereby leading to template leaching, which adversely affects real-world analytical applications. To overcome this challenge, the present study utilizes porogenic fragment template imprinting techniques to provide an alternative synthetic strategy to generate molecularly imprinted polymers with molecular recognition toward polychlorinated biphenyls. Thereafter, thus-generated imprinted polymers have been applied as stationary phases in molecularly imprinted solid-phase extraction for preconcentrating six “indicator polychlorinated biphenyls” in both organic and aqueous media. Recoveries of up to 98.9% (imprinted polymers) versus 73.0% (conventional C18) in an organic phase, and up to 97.4% (imprinted polymers) versus 89.4% (C18) in an aqueous phase have been achieved corroborating the utility of this advanced sorbent material. Finally, porogenic fragment template imprinting strategies have yielded molecularly imprinted polymers that are useful for the quantitative determination of polychlorinated biphenyls in environmental matrices, which provides a low-cost strategy for tailoring stationary phases that avoid template leaching in applications in solid-phase extraction as well as liquid chromatography.
Keywords: Gas chromatography